Supravalvular aortic stenosis-infantile hypercalcaemia syndrome: in vitro hypersensitivity to vitamin D2 and calcium. Issue 3 (June 1976) - Becroft, D M; Chambers, D
Abstract : The incidence of cytoplasmic metachromasia has been studied in cultures of skin fibroblasts derived from 6 cases of the syndrome of supravalvular aortic stenosis, characteristic facies, and mental retardation which in many instances represents the late normocalcaemic stage of the severe form of infantile hypercalcaemia. The percentage of metachromatic cells (mean positivity 7.3%) was significantly higher than in control cultures. The addition of vitamin D2 and calcium to culture media caused a highly significant increase in metachromatic cells (mean positivity in supplemented media 16.1%) compared with a lesser increase in controls. These findings strengthen previous suggestions that there is a genetically determined hypersensitivity to vitamin D in some cases of the syndrome. A multifactorial aetiology is proposed, dependent on a variable genetic susceptibility of fetal connective tissues to a non-physiological effect of D vitamins and a variable level of maternal vitamin D nutrition.